2017
DOI: 10.1002/acp.3312
|View full text |Cite
|
Sign up to set email alerts
|

What's Context Got to Do with It? Comparative Difficulty of Test Questions Influences Metacognition and Corrected Scores for Formula‐scored Exams

Abstract: On formula-scored exams students receive points and penalties for correct and incorrect answers, respectively, but they can avoid the penalty by withholding incorrect answers. However, test-takers have difficulty strategically regulating their accuracy and often set an overly conservative metacognitive response bias (e.g., Higham, 2007). The current experiments extended these findings by exploring whether the comparative difficulty of surrounding test questions (i.e., easy vs. hard)-a factor unrelated to the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
5
1
Order By: Relevance
“…Contrary to expectations, immediate feedback did not improve monitoring accuracy; monitoring accuracy was low with or without immediate feedback, and monitoring accuracy with immediate feedback was significantly less accurate than with no feedback (IF < NF, Cohen's d = .62, p = .012). A non-monotonic relationship between item performance and confidence was observed (hard-easy effect, Arnold et al, 2017;Juslin et al, 2000) that attenuates the findings here for relative monitoring accuracy (see Figure 2).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Contrary to expectations, immediate feedback did not improve monitoring accuracy; monitoring accuracy was low with or without immediate feedback, and monitoring accuracy with immediate feedback was significantly less accurate than with no feedback (IF < NF, Cohen's d = .62, p = .012). A non-monotonic relationship between item performance and confidence was observed (hard-easy effect, Arnold et al, 2017;Juslin et al, 2000) that attenuates the findings here for relative monitoring accuracy (see Figure 2).…”
Section: Discussioncontrasting
confidence: 55%
“…A premise of this investigation and perhaps of all SRL investigations is that of a monotonic relationship between the observed difficulty of the lesson content based on actual performance scores and the learner's judgement of the difficulty of that content -that difficult material is perceived to be difficult and easy material is perceived to be easy. But previous SRL research shows that students tend to be overconfident on difficult things and under confident on easy things, the hard-easy effect (Arnold, Graham, & Hollingworth-Hughes, 2017;Juslin, Winman, & Olsson, 2000). So what is perceived difficulty?…”
Section: Hard-easy Effectmentioning
confidence: 95%
“…However, from previous studies found that the test models developed in science tend to only focus on the aspects of knowledge, especially facts (M. M. Arnold, Graham, & Hollingworth-Hughes, 2017). In addition, the types of questions developed do not support the learning of science using the inquiry approach in the classroom.…”
Section: Introductionmentioning
confidence: 94%
“…Various factors, such as experience ( Cichoń et al 2018 ), feedback ( Iida et al 2020 ), and effort ( Lee and Daunizeau 2021 ) can affect individuals’ confidence judgments. The most important and common influencing factor is the item difficulty ( Arnold et al 2017 ; Clariana and Park 2021 ). The item difficulty significantly impacts the accuracy and confidence level of individual judgments, leading to a “hard-easy effect” on the accuracy of confidence judgments.…”
Section: Introductionmentioning
confidence: 99%